Tunable 2 µm ZrO2–Y2O3–Ho2O3 solid-state laser. (6th April 2017) - Ryabochkina, P A; Chabushkin, A N; Lyapin, A A; Lomonova, E E; Zakharov, N G; Vorontsov, K V
Abstract: ZrO2 –13.6 mol%Y2 O3 –0.4 mol%Ho2 O3 (YSZ:Ho) solid-state laser at 2130 nm under LiYF4 :Tm laser pumping was developed. The maximum output power of 5 W with a slope efficiency of 37% for continuous-wave operation was achieved. A tunable laser operating in the spectral range 2056–2168 nm on the YSZ:Ho crystals under LiYF4 :Tm laser pumping was demonstrated.